Association of migraine with calcification in major vessel beds: The Rotterdam Study. (July 2019) - Wen, Ke-xin; Ikram, Mohammad Arfan; Franco, Oscar H; Vernooij, Meike; MaassenVanDenBrink, Antoinette; Bos, Daniel; Kavousi, Maryam
Background: To explore the role of large-artery atherosclerosis in migraine, we investigated the association between migraine and arterial calcification in different intracranial and extracranial vessels. Methods: 1856 participants were included, mean age (standard deviation) 67.4 (5.8) years, from the population-based Rotterdam Study cohort. Migraine was assessed by validated questionnaire and vascular calcification was assessed by computed tomography (expressed in Agatston score for the coronary arteries and volume in mm 3 for the aortic arch, intracranial, and extracranial carotid arteries). Per vessel, the association of migraine with calcification was investigated by linear regression, adjusted for age, sex, cardiovascular risk factors, and calcification in other vessels. Results: Of the participants, 279 (15%) were identified as persons with lifetime migraine. In multivariable adjusted models, migraine was associated with smaller intracranial carotid artery calcification volume (difference in log-transformed calcification volume in persons with migraine compared to persons without migraine: −0.19[−0.29, −0.08]). While subjects with migraine also showed a lower calcification burden in the remaining arterial beds, those associations did not reach statistical significance. Conclusions: Persons with migraine, compared to those without, had less arterial calcification in the intracranial carotid artery, but not in other arterial beds. Future studies are needed to confirm these findings.